Prevalence of Urogenital Chlamydia Tracomatis Infection in Patients of Ectopic Pregnancy (Ibrahim Cardiac Medical Journal, 2025)
Background & objective: Ectopic pregnancy is not a rare complication of pregnancy, it is a significant obstetric concern,  for it often leads to acute emergencies due to potential rupture and hemorrhage. The incidence of ectopic pregnancy has  notably increased four-fold in recent decades, prompting investigations into emerging risk factors, particularly Urogenital  Chlamydia trachomatis infection. About one or two in every one hundred pregnancies are ectopic, often no reason is found.  This study aims to evaluate the prevalence of Chlamydia trachomatis among patients diagnosed with ectopic pregnancy.  Methods: This cross-sectional study was conducted from January to December 2004, involving 38 cases of confirmed ectopic  pregnancy, identified through clinical diagnosis and pelvic ultrasonography. Ethical approval was obtained from the  Institutional Review Board of the medical college, and informed consent was secured from all participants. Endocervical  swabs were collected and analyzed for Chlamydia trachomatis DNA using polymerase chain reaction (PCR) techniques. Data  on demographic and clinical variables were gathered using a semi-structured questionnaire and analyzed using descriptive  statistics through the Statistical Package for the Social Sciences (SPSS).  Result: The results showed that the mean age of participants was 24.3 years, with over half (55.3%) aged between 15 and  25 years. A significant portion of the population had a history of pelvic infections (60%) and previous abortions (26.3%). The  majority (92.1%) of the patients was confirmed to have an ectopic pregnancy. Despite the known association between  Chlamydia and ectopic pregnancy, only 5.3% of the patients tested positive for Chlamydia trachomatis. A high incidence of  anemia (over 60% with Hb < 50%) was noted among the participating patients. Most patients underwent surgical  interventions, primarily salpingectomy  Conclusion: This study highlights a concerning gap in the correlation between Chlamydia trachomatis infection and ectopic  pregnancy prevalence. Although the low detection rate of Chlamydia in this cohort suggests that it may not be a primary risk  factor in the local context, the significant history of pelvic infections indicates underlying etiological complexities. Future  research is necessary to explore other potential risk factors contributing to the rise in ectopic pregnancies, which may include  social, behavioral, and environmental influences. Improved awareness and early diagnosis of pelvic infections could play an  essential role in decreasing the incidence of ectopic pregnancies in Bangladesh. Ibrahim Card Med J 2024; 14(1): 62-66